Liver injury from Herbals and Dietary Supplements in the US Drug Induced Liver Injury Network - Navarro, Victor J. (Hepatology, 2014)
BACKGROUND: The Drug-Induced Liver Injury Network (DILIN) studies hepatotoxicity due to conventional medications as well as herbals and dietary supplements (HDS). RATIONALE: To characterize hepatotoxicity and its outcomes from HDS versus medications, patients with hepatotoxicity attributed to medications or HDS were enrolled prospectively between 2004 and 2013. The study took place among eight US referral centers that are part of the DILIN. Consecutive patients with liver injury referred to a DILIN center were eligible. The final sample comprised 130 (15.5%) of all subjects enrolled (839) who were judged to have experienced liver injury due to HDS. Hepatotoxicity due to HDS was evaluated by expert opinion. Demographic and clinical characteristics and outcome assessments including death and liver transplantation were ascertained. Cases were stratified and compared according to the type of agent implicated in liver injury; 45 had injury due to bodybuilding HDS, 85 due to non-bodybuilding HDS, and 709 due to medications. MAIN RESULTS: Liver injury due to HDS increased from 7% to 20% (p < 0.001) during the study period. Bodybuilding HDS caused prolonged jaundice (median 91 days) in young men but did not result in any fatalities or liver transplantation. The remaining HDS cases presented as hepatocellular injury, predominantly in middle-aged women and more frequently led to death or transplantation compared to injury from medications (13% vs. 3%, p < 0.05). CONCLUSIONS: The proportion of liver injury cases attributed to HDS in DILIN has increased significantly. Liver injury from non-bodybuilding HDS is more severe than from bodybuilding HDS or medications, as evidenced by differences in unfavorable outcomes; death and transplantation.